FISH-mapping of the 5S rDNA locus in chili peppers (Capsicum-Solanaceae) - Aguilera, Patricia Mabel; Debat, Humberto Julio; Scaldaferro, Marisel Analia; Marti, Dardo Andrea; Grabiele, Mauro (2018)
We present here the physical mapping of the 5S rDNA locus in six wild and fi ve cultivated taxa of Capsicum by means of a genus-specifi c FISH probe. In all taxa, a single 5S locus per haploid genome that persistently mapped onto the short arm of a unique metacentric chromosome pair at intercalar position, was found. 5S FISH signals of almost the same size and brightness intensity were observed in all the analyzed taxa. This is the fi rst cytological characterization of the 5S in wild taxa of Capsicum by using a genus-derived probe, and the most exhaustive and comprehensive in the chili peppers up to now. The information provided here will aid the cytomolecular characterization of pepper germplasm to evaluate variability and can be instrumental to integrate physical, genetic and genomic maps already generated in the genus.